2015
DOI: 10.1111/avsc.12193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding an arbuscular mycorrhizal fungi inoculum and of distance to donor sites on plant species recolonization following topsoil removal

Abstract: Questions: Does addition of an arbuscular mycorrhizal fungi (AMF) inoculum increase the short-term restoration success of nutrient-poor grassland (NPG) after topsoil removal? Does distance to intact remnant grassland (IRG) patches affect restoration success, and does the effect of inoculum addition depend on distance to IRGs?Location: Meerdaal forest, Oud-Heverlee, Belgium.Methods: In a topsoil-removed site of 8.5 ha, where 24 IRG patches (ca. 10% of the area) were kept, 48 plots (1 m 2 ) were established at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 63 publications
0
30
2
1
Order By: Relevance
“…These plots were situated next to the inoculated plots and close to a larger area of abundant heathland vegetation, which poses a significant source of heathland taxa available to colonize them. It has been shown that the vicinity of source sites is an important factor promoting heathland community development (Torrez et al , ; van der Bij et al , ). Surprisingly though, despite the fact that control plots collectively contained the majority of plant and fungal taxa observed in other treatments, including heathland taxa, the increase in the strength of links between heathland plants and fungi was notably delayed or absent compared with the sod‐inoculated plots.…”
Section: Discussionmentioning
confidence: 99%
“…These plots were situated next to the inoculated plots and close to a larger area of abundant heathland vegetation, which poses a significant source of heathland taxa available to colonize them. It has been shown that the vicinity of source sites is an important factor promoting heathland community development (Torrez et al , ; van der Bij et al , ). Surprisingly though, despite the fact that control plots collectively contained the majority of plant and fungal taxa observed in other treatments, including heathland taxa, the increase in the strength of links between heathland plants and fungi was notably delayed or absent compared with the sod‐inoculated plots.…”
Section: Discussionmentioning
confidence: 99%
“…for landscape restoration), or an unintended consequence. AMF inoculants have been shown to reduce plant biodiversity and/or prevent the establishment of native plants (Emam, 2016;Koziol, Bever, & Hawkes, 2015;Middleton et al, 2015;Torrez, Ceulemans, Mergeay, de Meester, & Honnay, 2016). Interestingly, inoculant provenance has been shown to be an important predictor of plant community response.…”
Section: Plant Biodiversitymentioning
confidence: 99%
“…Early in succession, effective AM fungal dispersal to and colonisation of sparsely vegetated sites may facilitate or 'drive' vegetation establishment (e.g. Torrez et al, 2016). Later in succession, when vegetation cover is closed and the availability of host plants is high, the mechanisms described by the passenger hypothesis may become more prevalent, that is, changes in plant community composition (e.g.…”
Section: Covariation Of Plant and Am Fungal Communitiesmentioning
confidence: 99%